Negosiasi Hukum Islam di Pulau Bawean: Studi Sistem Pembagian Harta Waris Adat dan Islam di Bawean - Ainul Yakin (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2019)
The topic of this article is the division of inheritance assets in Bawean Island in relation to Islamic inheritance law. This paper does not want to look for the legal status of the practice of division of inheritance on the island of Bawean according to Islam, but tries to elaborate the practice of the distribution of inheritance that exists on the island of Bawean. This type of research is qualitative with the case study method. While the theoretical framework used is Islamic inheritance law and maslahah. Data obtained through interviews and observations, and supplemented with secondary data such as Isalm inheritance book and customary law. The findings in this study indicate that the distribution system of inheritance on Bawean Island can be categorized as customary inheritance law, using two models of inheritance distribution. Namely the pattern du'um kupat and lalake mekol, bebine nyo’on. Both patterns are equally applied in the distribution of inheritance. The pattern of inheritance distribution with customary patterns is a form of negotiation between customary law and Islamic law. Once in Bawean there is already an official institution authorized to divide up inheritance assets such as the Religious Courts, but customary inheritance law is still maintained. The presence of codified Islamic inheritance law in the Compilation of Islamic Law (KHI) has not been fully followed in the practice of inheritance in Bawean. Between customary inheritance law and Islamic warsi law go hand in hand without eliminating them altogether. The practice of customary inheritance law among the Bawean community is still considered relevant in order to maintain kinship and family harmony. Thus, the provisions of Islamic inheritance law are implemented in an integrated manner without eliminating the others. Accommodation and negotiation are both in the context of harmonization between Islamic law and customary law as the benefit and local policy. Keywords: Customary law, inheritance, Islamic law, Maslahah